Application of Blocplan and Aldep Algorithms for Optimizing Production Layout at Meatball Factory - Thabed Tholib Baladraf (JTI: Jurnal Teknik Industri, 2025)
Layout is an element that must be considered in industrial design. A layout that considers the distance and proximity of departments will have better productivity. Facts on the ground show that there are still many industries that have not paid attention to this, one of which is the Meatball Manufacturing Factory, Brenggolo Street, Kediri. The purpose of this study is to minimize material handling costs while increasing productivity through improved design of meatball production facilities, analyze the sensitivity of layout changes, and compare the efficiency of the Blocplan algorithm and the Aldep algorithm in solving problems in meatball production by considering uncertainty. The method used in this study uses the Blocplan and Aldep algorithms, added with sensitivity analysis through several scenarios. The results showed that Blocplan and Aldep were able to provide recommendations for improving the layout of the meatball manufacturing factory's production facilities with good flow and efficient operational costs. Blocplan produces a cost of Rp. 1,366,761.6 or save 13.6% of the actual layout. While Aldep generates a cost of Rp. 797,040 or save 49.6% of the actual layout. In the sensitivity and Monte Carlo analysis, it was found that Aldep has the potential for future projection and has a near-perfect positive probability compared to Blocplan. This shows that the Aldep approach is a good and recommended layout proposal for the company. Keywords: Aldep; Blocplan; Layout; Material Handling Cost, Sensitivity